High Expression of Sphingosine Kinase 1 in Estrogen and Progesterone Receptors-Negative Breast Cancer - Azadeh Sadat Nazouri; omolbanin asadpour; Shahriar Dabiri; Bahram Pourseyedi; Mohamad reza Lashkarizadeh; Hamid Zeinalyneghad (Iranian Society of Pathology, 2017)
Background & objective: Breast cancer is the leading cause of cancer related death in females. Sphingosine kinase 1 (SPHK1) and its product sphingosine-1-phosphate (S1P) are the essential key regulator molecules in breast cancer through their ability to promote cell proliferation, angiogenesis, cell proliferation, and lymphagiogenesis. SPHK1 is overexpressed in multiple types of cancer including breast cancer and is associated with resistance to treatment. The current study aimed at investigating the expression of SPHK1 in estrogen and progesterone receptors (ER, PR) negative in comparison to ER, and PR positive breast cancer and their normal controls, and also finding the relationship between SPHK1 expression and high body index (BMI) in the selected groups with breast cancer. Methods: A total of 120 human breast cancer tissue specimens were analyzed for SPHK1 expression using quantitative real-time polymerase chain reaction (q RT-PCR) assay. Detection of hormonal status of breast cancer tissue samples was conducted by immunohistochemical assay. Result: The current study findings showed that the level of SPHK1expression in the breast cancer tissue was significantly higher in patients with estrogen and progesterone negative receptors, compared to the ones without them (P-value< 0.05). The obtained data confirmed that the obesity in patients with ER negative was higher than the ones with positive receptors (BMI> 25). Conclusion: The current study showed that expression of SPHK1gene was higher in the patients with ER and PR negative breast cancer and high BMI, compared with other groups.